FACTORS THAT INFLUENCE CESAREAN SECTION DELIVERIES IN INDONESIA - Septiana Lazasniti; Putri Bungsu Machmud; Sudarto Ronoatmodjo (Universitas Airlangga, 2020)
Background: The percentage of cesarean deliveries in Indonesia increased from 12% in 2012 to 17% in 2017. Purpose: The aim of this study was to determine the factors that influenced the rate of cesarean deliveries in Indonesia in 2017. Method: The study used a cross-sectional design, gathering secondary data from the Indonesian Health Demographic Survey (IDHS) in 2017. The sample included mothers who gave birth to their last child in Indonesia in the last five years; a survey was conducted after respondents with missing data were excluded. The selection of samples was based on the availability of data in the IDHS 2017 dataset (8,683 respondents). A stratified two-stage sampling method was used. Data were gathered through a household questionnaire and a women of childbearing age questionnaire. Univariate, bivariate, and multivariate analyses were conducted using the chi-squared test and a simple logistic regression. Results: The factors that influenced the rate of cesarean section deliveries in Indonesia in 2017 were birth attendants (p value = 0.01; PR = 3.12; 95% CI = 2.88–3.38), number of Antenatal Care (ANC) visits (p=0.02; PR=1.23; 95%CI=1.03–1.47), low wealth index (p=0.02; PR=0.89; 95%CI=0.81–0.98), place of delivery (p=0.01; PR=0.87; 95%CI=0.81–0.94), and ANC provider (p=0.01; PR=0.57; 95%CI=0.53–0.62). The results of the analyses also obtained confounding factors; namely, parity and birth interval. Conclusion: Factors that influenced cesarean delivery in Indonesia in 2017 were a low wealth index, number of ANC visits, ANC provider, place of delivery, and birth attendants.